Increased attention in ADHD (Attention-Deficit Hyperactivity Disorder) children using media based video in English language lessons - Nurhidayati, Fitri (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
English language learning in Indonesia began in childhood, namely playing groups. English is a foreign language in Indonesia and has not become a second language. For Indonesian people, English is considered difficult to learn because of the differences in rules and procedures. Especially for ADHD children. they tend to be active and need their own techniques to attract their attention. Meanwhile, based on the government policies ADHD children is accepted in public schools. The teacher usually treats ADHD children the same with non ADHD students. For this reason, the study aims to examine the increasing concentration of learning for ADHD children with media based video. This study used a qualitative descriptive study with ADHD children in eleventh-grade vocational school. After being examined, children with ADHD tend to be calmer and after several treatments, children with ADHD could also produce simple utterance related to the topic and more longer attention.Â DOI: 10.26905/enjourme.v2i2.2857Â